Simplicity of Lyapunov spectrum for linear cocycles over non-uniformly hyperbolic systems - BACKES, LUCAS; POLETTI, MAURICIO; VARANDAS, PAULO; LIMA, YURI (Ergodic theory and dynamical systems, 2020)
We prove that generic fiber-bunched and Hölder continuous linear cocycles over a non-uniformly hyperbolic system endowed with a $u$-Gibbs measure have simple Lyapunov spectrum. This gives an affirmative answer to a conjecture proposed by Viana in the context of fiber-bunched linear cocycles.